Response to the Use of Radio Channels as Online Learning Media in Elementary Schools - Rini Widyastuti; Tria Mardiana; Ari Suryawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The study aims to know the response of parents and teachers regarding the use of radio channels as online learning media in SD Negeri Paremono 1 Kecamatan Mungkid. The study uses qualitative comparisons with case studies. The data comes from 11 pairs of students, 11 parents plus 6 teachers from class I through class VI. During the data collection stage, researchers use interviewing methods, observation and angkets. Testing the validity of data, researchers used technical triangulation (interviews, observations, digitation of documents and angkets) as well as source triangulation (students, parents and teachers). Data analysis runs through four components, that is: data collection, data reduction, data presentation and deduction deduction. The results of this study indicate that the students' responses is good, the parents' response is also good, while the teacher’s response is also good. This is because the three data sources have clear information on executing online learning using radio channel media, preparations are made to a maximum and when the application is not absolute. As a learning evaluation, students usually get assignments, both online and offline. Online tasks are given and collected daily through the whatsapp/googleform. While the task is offline twice a week, students take and collect assignments on Mondays and Thursdays.